Application of Bruner Theory and Local Culture to Improve Numeracy Skills of Elementary School Students Assigned to The Teaching Campus Program Batch 7 of 2024 - Desti Haryani; Qodri Ali Hasan; Jackson Pasini Mairing; Belen Amelda Yohan Jeniva; Oloan Saputra Sinambela (JURNAL PENDIDIKAN, 2025)
This research is motivated by the low numeracy skills of elementary school students (SD) where the Campus Teaching Program Batch 7 of 2024 was assigned. The low numeracy skills are closely related to the understanding of elementary school students' mathematical concepts, especially those related to integer operations (addition, subtraction, multiplication, and division). This research is intended to inform learning models that aim to improve students' numeracy skills. The research method used is descriptive research using a case study method with a qualitative-quantitative approach. The subjects of this study were 16 students of class VI of SDN 3 Palangka and 21 students of class V of SDN 11 Palangka. Data collection was carried out by observation, tests, and questionnaires. The results of this study, after the implementation of learning by applying Bruner's Theory and local culture, there was an increase in student activity, students became more active in class. The results of student learning with an average value of students' integer operation skills at SDN 3 Palangka was 63.66 and the average value of students' numeracy skills was 45.19. Meanwhile, the average value of students' integer operations ability at SDN 11 Palangka is 70.33 and the average value of students' numeracy ability is 75.85. Students' responses to learning with the application of Bruner's theory obtained an average percentage of 99.57% with high criteria, which means that most students gave a positive response to the application of Bruner's theory in mathematics learning, especially the material on integer arithmetic operations.